ФАРҒОНА БОТИҒИ ЛАНДШАФТЛАРИНИ ЗАМОНАВИЙ УСУЛЛАРДА ТАДҚИҚ ЭТИШ ҲАМДА УЛАР АСОСИДА ЛАНДШАФТЛАРДАГИ ЎЗГАРИШЛАРНИ БАҲОЛАШ - Қўзибоева, О. (SCIENCE and SOCIETY, 2021)
In the current age of science and technology, the use of modern technologies in all spheres of human activity, including agriculture, especially in the use of satellite images.Based on the decoding of satellite images, the main indicator of landscapes is determined and the analysis of their dynamic changes and monitoring of the future geoecological situation is highlighted.